قياس مستوى جودة الخدمات الفندقية المقدّمة في فنادق محافظة اللاذقية من وجهة نظر النزلاء (دراسة حالة فندق أفاميا( - نصور, ريزان; إبراهيم, نور (Latakia University Journal - Economic and Legal Sciences Series, 2017)
هدفت الدراسة إلى التعرّف على مستوى جودة الخدمات الفندقية المقدمة في فنادق اللاذقية، ومعرفة مستوى رضى النزلاء المستفيدين من جودة هذه الخدمات، إلى جانب تحديد مدى اختلاف تقييم النزلاء للأداء الفعلي للخدمات الفندقية المقدّمة في فندق أفاميا وفقاً لأبعاد جودة الخدمة الفندقية، وقد اتبعت الباحثة أسلوب دراسة الحالة، حيث استخدمت لذلك المنهج الوصفي التحليلي لقياس جودة الخدمات المدركة والفعلية، وتمّ تصميم وتوزيع استبانة على نزلاء المنشأة الفندقية المدروسة بغية قياس درجة جودة الخدمات، كما تمّت دراسة وتحليل البيانات باستخدام برنامج spss، وبعد تحليل البيانات أظهرت النتائج أنّ استجابات عينة الدراسة نحو قياس جودة الخدمات الفعلية والمدركة من قبل النزلاء كانت متوسطة غالباً وفقاً لأبعاد جودة الخدمات الفندقية (الملموسية، الاعتمادية، الاستجابة، الثقة والأمان، التعاطف)، وقدّمت الدراسة مجموعة من التوصيات كان من ضمنها بذل كافة الجهود الضرورية لنشر ثقافة الجودة وتعزيزها داخل المنشأة الفندقية، وتوفير الرعاية الشخصية بالعميل عبر الدقة في الأداء والسرعة في التنفيذ واللباقة في المعاملة، بالإضافة إلى وضع خطة استراتيجية خاصّة بتطبيق الجودة في المنشأة الفندقية المدروسة.This study aimed to identify service quality level provided at hotels in Lattakia from the guests' point of view. It also determined the satisfaction level of beneficiaries of hotel services provided in research community and how guests evaluate the actual performance of the hotel services provided at Afamia Rotana Hotel according to the quality hotel services dimensions differently.The research community consisted of Afamia Rotana Hotel guests. The researcher has used the case study method and depended on descriptive approach to measure the satisfaction of the beneficiaries with the quality of hotel services provided in the hotel. A survey has been designed and distributed among the guests in order to measure the quality level of hotel services in the research community. Then the researcher analyzed the survey results by the Statistical Package for the Social Sciences (SPSS). The research concluded that there was a clearly lack of quality of hotel services provided at the research community according to the dimensions of quality of hotel services (tangibility, reliability, power of responsiveness, empathy, trust and safety).So the study has provided a set of recommendations, including making more efforts to spread the quality culture at hotels, taking care of customers personally through the accuracy of the performance, speed of implementation and courteous treatment, in addition to developing a quality strategic plan in the research community.